Lean Manufacturing in food production: Systematic review, bibliometric analysis and proposed application - Ferrer-Blas, Rosita Iselda (2024)
In a changing environment, efficiency and adaptability are essential to improve business competitiveness. The present study analyzed the application of Lean Manufacturing in food production through a review of the scientific literature based in Scopus, using the PRISMA methodology and the Vosviewer and Bibliometrix software. From the bibliometric analysis, there is evidence of an increase in research on Lean Manufacturing in food companies since 2019, with an annual growth rate of 5.96%. Brazil and Peru stand out for their high scientific production, while Brazil and Belgium stand out in terms of citations. In addition, outstanding scientific collaboration between authors from South America and Asia is observed. Three relevant clusters were identified: principles, implementation tools and practical applications of Lean Manufacturing. The thematic mapping highlighted the concepts Cost Reduction, Process Monitoring, Six Sigma and Value Stream Mapping as the most prominent topics underlining the interest and applications in the scientific literature. The implementation of Lean Manufacturing in seven steps is proposed, facilitating the use of agile tools for process optimization and waste reduction in food companies. Lean Manufacturing contributes to improve the flow of products in the supply chain and to the sustainability of small and medium enterprises. Future research should focus on adapting Lean Manufacturing to various contexts and business models in the agri-food sector.